Hepatic epithelioid hemangioendothelioma successfully treated with living donor liver transplantation: A case report and literature review. Issue 1 (17th December 2019) - Fukuhara, Sotaro; Tahara, Hiroyuki; Hirata, Yoshito; Ono, Kosuke; Hamaoka, Michinori; Shimizu, Seiichi; Hashimoto, Shinji; Kuroda, Shintaro; Ohira, Masahiro; Ide, Kentaro; Kobayashi, Tsuyoshi; Ohdan, Hideki
Abstract: Hepatic epithelioid hemangioendothelioma is a rare neoplasm with a variable malignant potential and a high risk of recurrence. No general treatment guidelines have been established. Fortunately, we were able to minimize immunosuppressant after liver transplantation because of a full HLA‐matched case. There was no recurrence 1 year after treatment. Abstract : Hepatic epithelioid hemangioendothelioma is a rare neoplasm with a variable malignant potential and a high risk of recurrence. No general treatment guidelines have been established. Fortunately, we were able to minimize immunosuppressant after liver transplantation because of a full HLA‐matched case. There was no recurrence 1 year after treatment.